Struggle To Survive: the Choir of Target Alteration, Hydrolyzing Enzyme, and Plasmid Expression as a Novel Aztreonam-Avibactam Resistance Mechanism - Ke Ma (American Society for Microbiology, 2020)
ABSTRACT Aztreonam-avibactam is a promising antimicrobial combination against multidrug-resistant organisms, such as carbapenemase-producing Enterobacterales. Resistance to aztreonam-avibactam has been found, but the resistance mechanism remains poorly studied. We recovered three Escherichia coli isolates of an almost identical genome but exhibiting varied aztreonam-avibactam resistance. The isolates carried a cephalosporinase gene, blaCMY-42, on IncIγ plasmids with a single-nucleotide variation in an antisense RNA-encoding gene, inc, of the replicon. The isolates also had four extra amino acids (YRIK) in penicillin-binding protein 3 (PBP3) due to a duplication of a 12-nucleotide (TATCGAATTAAC) stretch in pbp3. By cloning and plasmid-curing experiments, we found that elevated CMY-42 cephalosporinase production or amino acid insertions in PBP3 alone mediated slightly reduced susceptibility to aztreonam-avibactam, but their combination conferred aztreonam-avibactam resistance. We show that the elevated CMY-42 production results from increased plasmid copy numbers due to mutations in inc. We also verified the findings using in vitro mutation assays, in which aztreonam-avibactam-resistant mutants also had mutations in inc and elevated CMY-42 production compared with the parental strain. This choir of target modification, hydrolyzing enzyme, and plasmid expression represents a novel, coordinated, complex antimicrobial resistance mechanism and also reflects the struggle of bacteria to survive under selection pressure imposed by antimicrobial agents. IMPORTANCE Carbapenemase-producing Enterobacterales (CPE) is a serious global challenge with limited therapeutic options. Aztreonam-avibactam is a promising antimicrobial combination with activity against CPE producing serine-based carbapenemases and metallo-β-lactamases and has the potential to be a major option for combatting CPE. Aztreonam-avibactam resistance has been found, but resistance mechanisms remain largely unknown. Understanding resistance mechanisms is essential for optimizing treatment and developing alternative therapies. Here, we found that either penicillin-binding protein 3 modification or the elevated expression of cephalosporinase CMY-42 due to increased plasmid copy numbers does not confer resistance to aztreonam-avibactam, but their combination does. We demonstrate that increased plasmid copy numbers result from mutations in antisense RNA-encoding inc of the IncIγ replicon. The findings reveal that antimicrobial resistance may be due to concerted combinatorial effects of target alteration, hydrolyzing enzyme, and plasmid expression and also highlight that resistance to any antimicrobial combination will inevitably emerge.